Analisis Strategi Pemasaran Produk Wardah - Dindha Tria Lestari; Novianti Novianti; Syamsul Hidayat (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the marketing strategy of Wardah, a leading cosmetic brand in Indonesia. The main focus of the research is to identify the effectiveness of Wardah’s marketing strategies in boosting sales and customer loyalty. The research employs a descriptive quantitative method by distributing questionnaires to respondents who are Wardah consumers. The collected data were analyzed using descriptive statistical techniques to describe the relationship between marketing strategies and consumer behavior. The findings reveal that digital-based marketing strategies, product quality, and Islamic brand image significantly influence customer satisfaction and loyalty. These findings are expected to serve as a reference for depeloping more effective marketing strategies.